The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamaophthalmol.2022.1563
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Retinal Layer Thickness and Cognitive Decline in Older Adults

Abstract: IMPORTANCERetinal layer thickness is hypothesized to be related to cognitive function in patients with mild cognitive impairment (MCI) and Alzheimer disease (AD). However, longitudinal cohort studies of the healthy older population are scarce.OBJECTIVE To investigate the association between retinal layer thickness and cognitive impairment and future cognitive decline in a community-based population cohort.DESIGN, SETTING, AND PARTICIPANTS A total of 430 randomly sampled community-dwelling Korean individuals 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In our present study, we showed retinal thicknesses and retinal microvasculature had a significant correlation with Stroop parameters which is in line with previous reports ( van Koolwijk et al, 2009 ; Mutlu et al, 2018 ). Our findings suggest that GCIPL thickness and SVC density may reflect cognitive dysfunction which is in line with previous reports ( Jones-Odeh et al, 2016 ; Ko et al, 2018 ; Girbardt et al, 2021 ; Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our present study, we showed retinal thicknesses and retinal microvasculature had a significant correlation with Stroop parameters which is in line with previous reports ( van Koolwijk et al, 2009 ; Mutlu et al, 2018 ). Our findings suggest that GCIPL thickness and SVC density may reflect cognitive dysfunction which is in line with previous reports ( Jones-Odeh et al, 2016 ; Ko et al, 2018 ; Girbardt et al, 2021 ; Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Using different ophthalmic imaging tools, studies have shown patients with dementia and mild cognitive impairment (MCI) have significantly thinner peripapillary retinal nerve fiber layer (pRNFL), macular retinal nerve fiber layer (mRNFL), and ganglion cell-inner plexiform layer (GCIPL) and/or ganglion cell complex (GCC) and microvascular impairment compared to controls without cognitive decline ( Alber et al, 2020 ; Cheung et al, 2021 ). Structural retinal imaging studies on the elderly population showed thinner RNFL thicknesses and retinal microvascular impairment could indicate cognitive impairment and future cognitive decline over time ultimately resulting in an increased risk of dementia ( Ko et al, 2018 ; Kim et al, 2022 ). Previous reports reported on either the retinal structure or the retinal microvasculature and its association with cognitive measures (either Montreal Cognitive Assessment, MoCA, or Mini-Mental State Examination, MMSE) in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…6 In a community-based population cohort of 430 Koreans aged 60 years or older, 215 individuals completed a 5.4-year mean follow-up; participants with a baseline mRNFLT below the lowest quartile cutoff had a greater decline in cognitive scores and a higher prevalence of cognitive impairment and AD compared with those with an RNFLT above the lowest quartile cutoff. 23 Our study results suggest that monitoring RNFLT in a hypertensive population and using it as a basis for assessing their risk of developing dementia is extremely important. Future studies should assess the predictive strength of RNFLT for the risk of dementia in hypertensive patients to provide more robust evidence for further dissemination of this finding in the clinical setting.…”
Section: Discussionmentioning
confidence: 82%
“…However, a recent 2022 study by Kim et al noted that macular RNFL thinning may even precede peripapillary RNFL thinning and may be a prognostic biomarker of cognitive decline in older individuals. The authors followed patients aged > 60 and found a strong association between decreased cognitive function test scores and thinner macular retinal nerve fiber layer [ 50 ]. Moreover, Lopez-Cuenca et al examined the macular retinal thickness and peripapillary RNFL in healthy cognitive subjects at high genetic risk of developing AD, comparing them to age-matched controls.…”
Section: Ocular Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%